Ecotorismo os atrativos naturais em Bujaru/Pará - SILVA, Gelson Carneiro da (Universidade Federal do Pará, 2020)
Ecotourism is a segment of tourism that is growing increasingly and has contributed to the economic and social development of the town. This is because it shows how a potential for improving the lives of the communities involved, in addition to the protection, conservation and environmental preservation. Alternatively recreation, ecotourism, based on the triad of sustainable development (preservation and conservation of the environment, development and involvement of village community and economic growth) is not limited to the sustainable use of natural now, but make the search minimization the consequences of the flow of tourists, drawing up of a control the ability to support the town, serving as the basis for monitoring the environmental degradation that the flow of tourists can provide the environment visited. In this article we present how this method has been developed in the municipality of Bujaru and their surroundings